GLACIAL CATASTROPHE OF 20 SEPTEMBER 2002 IN NORTH OSETIA - Drobyshev V.N. (My University, 2006)
The aim of this study was to reconstruct the main parameters of the catastrophe, using the data obtained as a result of instrumental measurements. The parameters of the catastrophe were estimated, and the volumes of the collapsed firn massif and body of the Kolka Glacier were calculated. Also reported in this paper are the results of the topographic monitoring of the glacier barrier in the Karmadon Basin. Using the seismic records available, the speed of the glacier demolition down the Genaldon Ravine was calculated. It is assumed that the main cause that had initiated the beginning of the catastrophic process was the seismic effect resulting in the origin of fumarolic emanations under the firn field in July 2002 (two months before the catastrophe) and its gradual destruction in the course of termocarst development.
Keywords: MOUNTAIN GLACIERS; FIRN MASSIFS; AVALANCHES; LANDSLIDES; EARTHQUAKES